S. aureus and MRSA nasal carriage in dental students: a comprehensive approach - Cavaco-Silva, Patrícia (2021)
Staphylococcus aureus and MRSA are important clinical pathogens representing a serious public health problem. This study aimed to determine the prevalence of S. aureus and methicillin-resistant S. aureus (MRSA) nasal carriage among dental students, identify the factors that influence this carriage, and characterize MRSA. A prevalence of S. aureus and MRSA carriage of 25.2% and 0.86% was estimated, respectively, and SCCmec Type VI, was identified in all isolated MRSA. The low MRSA colonization rate can reflect good infection control practices followed by students.